Role of Research in Manufacturing and Processing Asadded Value to the Economy (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to cast some shadow on the policies of research with regards to socio-economicdevelopment of the nation. It will high light some points for taking the results of scientific and technologicalstudies from the research level to implementation at the business level. It will specifically emphasize how torealizethe added value to the economy by applying scientific and technological knowledge in manufacturing andprocessing of agriculturalcrops and other raw materials available in the country.